Contribution of Financial Performance to Profit Growth In the Primary Goods Retail Trade Subsector Companies - Sirait, Clara Victoria; Paranita, Ekayana Sangkasari (The Graduate School of Sahid University, 2024)
This research aims to determine the contribution of financial performance to Profit Growth. Financial performance is measured based on liquidity, solvency, profitability, and activity ratios, while CAGR (Compound Annual Growth Rate) measures profit growth. The research object is primary goods retail trading subsector companies listed on the Indonesia Stock Exchange in 2019-2022 when this subsector experienced fluctuations in profit growth. The research population was 13 primary goods retail trade subsector companies. Based on purposive sampling, 10 companies met the criteria, so there were 40 observations in 4 years. The data analysis technique is panel data regression. The model estimation test shows that the Fixed Effect Model is the best model in this research. The research findings show that partially the Current Ratio, Debt to Equity Ratio, Return On Equity, and Total Asset turnover do not have a significant effect on profit growth. Still, simultaneously all of these independent variables have a significant effect on profit growth.